The Protozoan Inhibitor Atovaquone Affects Mitochondrial Respiration and Shows In Vitro Efficacy Against Glucocorticoid-Resistant Cells in Childhood B-Cell Acute Lymphoblastic Leukaemia - Sbirkov, Yordan; Ivanova, Tsvetomira; Burnusuzov, Hasan; Gercheva, Kalina; Petrie, Kevin; Schenk, Tino; Sarafian, Victoria (Frontiers in Oncology, 2021)
Childhood acute lymphoblastic leukaemia (cALL) accounts for about one third of all pediatric malingnancies making it the most common cancer in children. Alterations in tumuour cell metabolism were first described nearly a century ago and have been acknowledged as one of the key characteristics of cancers including cALL. Two of the backbone chemotherapeutic agents in the treatment of this disease, Glucocorticoids and L-asparaginase, are exerting their anti-leukaemic effects through targeting cell metabolism. Even though risk stratification and treatment regiments have improved cure rates to nearly 90%, prognosis for relapsed children remains poor. Therefore, new therapeutic approaches are urgently required. Atovaquone is a well-tolerated drug used in the clinic mainly against malaria. Being a ubiquinone analogue, this drug inhibits co-enzyme Q10 of the electron transport chain (ETC) affecting oxidative phosphorylation and cell metabolism. In this study we tested the effect of Atovaquone on cALL cells in vitro. Pharmacologically relevant concentrations of the inhibitor could effectively target mitochondrial respiration in both cALL cell lines (REH and Sup-B15) and primary patient samples. We found that Atovaquone leads to a marked decrease in basal respiration and ATP levels, as well as reduced proliferation, cell cycle arrest and induction of apoptosis. Importantly, we observed an enhanced anti-leukaemic effect when Atovaquone was combined with the standard chemotherapeutic Idarubicin, or with Prednisolone in an in vitro model of Glucocorticoid resistance. Repurposing of this clinically-approved inhibitor renders further investigations, but also presents opportunities for fast-track trials as a single agent or in combination with standard chemotherapeutics.